Harnessing joint distraction for the treatment of osteoarthritis: a bibliometric and visualized analysis - Peng, Liqing; Li, Runmeng; Xu, Shengxi; Ding, Keyuan; Wu, Yan; Li, Hao; Wang, Yong (Frontiers in Bioengineering and Biotechnology, 2023)
Osteoarthritis (OA) stands as a prevalent degenerative joint ailment, demanding immediate attention towards the development of efficacious therapeutic interventions. Presently, a definitive cure for OA remains elusive, and when conservative treatment modalities prove ineffective, resorting to a joint prosthesis becomes imperative. Temporary distraction emerges as a pivotal joint-preserving intervention in human OA patients, conferring both clinical amelioration and structural enhancements. Although extant clinical investigations exist, they are characterized by relatively modest sample sizes. Nonetheless, these studies furnish compelling evidence affirming that joint distraction engenders sustained clinical amelioration and structural refinement. Despite substantial strides in the last decade, a bibliometric analysis of joint distraction within the realm of osteoarthritis treatment research has been conspicuously absent. In this context, we have undertaken a comparative investigation utilizing bibliometric methodologies to scrutinize the landscape of joint distraction within osteoarthritis treatment. Our comprehensive analysis encompassed 469 scholarly articles. Our findings evince a consistent escalation in global research interest and publication output pertaining to this subject. The United States emerged as the frontrunner in international collaboration, publication count, and citation frequency, underscoring its preeminence in this domain. The journal "Osteoarthritis and Cartilage" emerged as the principal platform for disseminating research output on this subject. Notably, Mastbergen SC emerged as the most prolific contributor in terms of authorship. The identified keywords predominantly revolved around nonsurgical interventions and joint arthroscopy procedures. This bibliometric analysis, augmented by visual representations, furnishes invaluable insights into the evolutionary trajectory of joint distraction as an osteoarthritis treatment modality spanning from 2003 to 2023. These insights will serve as a compass for the scientific community, facilitating further exploration in this promising domain.